CarbonIron Electron Transport Channels in Porphyrin–Graphene Complex for ppb‐Level Room Temperature NO Gas Sensing. Issue 11 (20th January 2022) - Gao, Yixun; Wang, Jianqiang; Feng, Yancong; Cao, Nengjie; Li, Hao; de Rooij, Nicolaas Frans; Umar, Ahmad; French, Paddy J.; Wang, Yao; Zhou, Guofu
Abstract: It is a great challenge to develop efficient room‐temperature sensing materials and sensors for nitric oxide (NO) gas, which is a biomarker molecule used in the monitoring of inflammatory respiratory diseases. Herein, Hemin (Fe (III)‐protoporphyrin IX) is introduced into the nitrogen‐doped reduced graphene oxide (N‐rGO) to obtain a novel sensing material HNG‐ethanol. Detailed XPS spectra and DFT calculations confirm the formation of carbon–iron bonds in HNG‐ethanol during synthesis process, which act as electron transport channels from graphene to Hemin. Owing to this unique chemical structure, HNG‐ethanol exhibits superior gas sensing properties toward NO gas ( R a / R g  = 3.05, 20 ppm) with a practical limit of detection (LOD) of 500 ppb and reliable repeatability (over 5 cycles). The HNG‐ethanol sensor also possesses high selectivity against other exhaled gases, high humidity resistance, and stability (less than 3% decrease over 30 days). In addition, a deep understanding of the gas sensing mechanisms is proposed for the first time in this work, which is instructive to the community for fabricating sensing materials based on graphene‐iron derivatives in the future. Abstract : The unique carboniron bonds formed through decarboxylation and electrostatic interaction during the synthesis process of the Hemin‐N‐rGO composites provide efficient electron transport channels from graphene to Hemin, and play a key role in the sensing process of this material, which realize excellent performance toward NO gas at room temperature.